PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN POS LINTAS BATAS (PLB) DI DESA SUNGAI KELIK KECAMATAN KETUNGAU HULU KABUPATEN SINTANG - Nikodimus, Nikodimus (Universitas Kapuas Sintang, 2024)
Development of border areas is the main program carried out by the government to open access in border areas. Currently, the government is very focused on developing border areas, one of which is by opening border crossing posts between countries. The development of this cross-border post is carried out so that it can have an impact on countries, regions and villages that have coordinate points in the construction of the Cross-Border Post itself. The construction of the National Border Post in Sungai Kelik Village is the hope and dream of the people in Sungai Kelik Village. Moving on from this problem, the author conducted research regarding Community Participation in the Construction of Cross-Border Posts in Sungai Kelik Village, Ketungau Hulu District, Sintang Regency. The aim of this research is to analyze and describe community participation in the construction of a cross-border post in Sungai Kelik Village. The results of this research are related to Community Participation in the Construction of the National Cross-Border Post in Sungai Kelik Village. The local community fully supports the construction of the Cross-Border Post because they hope it can provide benefits, especially in terms of improving the economy and various access to development that can be directly felt by the community, such as availability. road infrastructure and communication access. Some of the community's hopes are related to the existence of a Cross-Border Post in Sungai Kelik Village, when it operates in the future, it can utilize local community resources to be employed at the Cross-Border Post Abstak: